Influence of ambient conditions on the marine two-stroke engine integrated with a bottoming Rankine cycle system: Energy and exergy analyses. (25th January 2023) - Zhu, Sipeng; Feng, Jinfeng; Tang, Yujun; Bai, Shuzhan; Deng, Kangyao
Highlights: Influence of ambient conditions on the combined cycle was studied theoretically. Different engine tuning strategies were compared at varied ambient temperatures. The high-pressure tuning makes almost no influence on exergy distributions. The bypass tuning can effectively control the exhaust gas temperature. The performance of the combined cycle deteriorates with the increasing ambient temperature. Abstract: The varied ambient condition brings challenges to highly efficient operation of the marine engine especially when a bottoming Rankine cycle system is integrated. However, few theoretical studies on it were reported. This paper aims at providing a comprehensive energy and exergy study on the marine two-stroke engine and its integrated bottoming Rankine cycle operating at different ambient temperatures. First, the thermodynamic processes of the combined cycle power plant and its tuning methods are described in detail, followed by model building and validation. Parametric studies on the combined cycle power plant operating under varied ambient conditions are then performed from energy and exergy perspectives. It is concluded that the high-pressure tuning can effectively control the scavenging process under varied ambient conditions but has a limited effect on the exergy distributions of the marine engine. With the bypass tuning, every 10 °C rise in the ambient temperature requires a decrease of the bypass ratio by 2% in absolute, which increases the exhaust gas temperature by only 5 °C compared to that of 16 °C in the base engine case. In the bottoming Rankine cycle system, the optimum evaporation pressure is mainly determined by the exhaust temperature rather than the ambient temperature. The fuel-saving potential of the combined cycle with the power turbine tuning reaches up to 7% and is deteriorated with the increasing ambient temperature.